PERSAMAAN DERAJAT TERHADAP PEMBAGIAN HAK WARIS ANAK DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - Abidah, Atik (Fakultas Syariah, 2014)
This research aims to analyze the equality rights of biological children in the decision of the Constitutional Court of the Republic of Indonesia number: 46/PUU-VIII/2010 and its legal consequence. This research included in the normative legal research that used a statue approach and case study approach. The research’s data analyzed using preskriptive-analytic methode and hermeneutic methode. The Research’s results showed that the decision of Constitutional Court of the Republic of Indonesia number: 46/PUU-VIII/2010 expand the interpretation of the concept of nasab from legal children towards biological children to achieve the equality and the sense of fairness. This verdict also expand the interpretation of the evidence. The relationship between parents and their childrens can be proved with the aid of science and technology. The similarity of DNA / RNA betwen parents and their childern is the ratio legis ('illat al-hukm) that into consideration the biological children acquire the civil rights, including inheritance rights.